2007
DOI: 10.1088/1741-2560/4/2/013
|View full text |Cite
|
Sign up to set email alerts
|

Trophic factor induction of human umbilical cord blood cellsin vitroandin vivo

Abstract: The mononuclear fraction of human umbilical cord blood (HUCBmnf) is a mixed cell population that multiple research groups have shown contains cells that can express neural proteins. In these studies, we have examined the ability of the HUCBmnf to express neural antigens after in vitro exposure to defined media supplemented with a cocktail of growth and neurotrophic factors. It is our hypothesis that by treating the HUCBmnf with these developmentally-relevant factors, we can expand the population, enhance the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 80 publications
0
20
1
1
Order By: Relevance
“…Unfortunately, the morphology of these cells does not fully support their suggested neuronal phenotype. A recent study from our lab has shown that the floating cells possess greater proliferation capacity and more neural characteristics than the adherent fraction of cells [5]. Such a distinction was not made in any major capacity in this study and may contribute to this.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Unfortunately, the morphology of these cells does not fully support their suggested neuronal phenotype. A recent study from our lab has shown that the floating cells possess greater proliferation capacity and more neural characteristics than the adherent fraction of cells [5]. Such a distinction was not made in any major capacity in this study and may contribute to this.…”
Section: Discussioncontrasting
confidence: 50%
“…Our study would appear to support this, since the absence of an immunogenic background in the NOD/SCID mice did not aid survival. Chen et al [5] also demonstrated enhanced proliferation and survival following growth factor treatment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As one potential source of neural stem cells, CBMNCs contain various progenitor cells including a large population of CD34 + hematopoietic stem cells, a small population of mesenchymal stem cells, and very few endothelial progenitor cells and muscle satellite cells. These progenitor cells are highly proliferative with the potential to differentiate towards a neural cell fate, and secrete various growth and neurotrophic factors (Fan et al, 2005;Habich et al, 2006;Chen et al, 2005Chen et al, , 2007Lee et al, 2007;Bachstetter et al, 2008). These factors, when secreted into the immediate extracellular environment, play important roles in paracrine signaling to regulate hematopoietic processes, immune responses, angiogenesis, and cell proliferation, differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The capability of mononuclear hUCB cells to express neural antigens has recently been determined following in vitro exposure to media supplemented with a cocktail of growth and neurotrophic factors. When the floating mononuclear fraction of hUCB cells was exposed to a neurogenic circumstance by treatment with growth factors and neurotrophins, this fraction of cell increased their proliferation and expression of neural antigens, and they also survived longer in vivo [67].…”
Section: Transdifferentiation Into Neural Lineagesmentioning
confidence: 99%